A Dataset Augmentation Method for Non-convergent Power Flow Adjustment Behavior Based on Improved Conditional Generative Adversarial Network - Wu, X.; Zhang, L.; Xu, S.; Qian, J. F.; Li, Q. (Advanced Electromagnetics, 2026)
This paper proposes a data augmentation method for generating non-convergent power flow adjustment behavior datasets based on an improved generative adversarial network. Firstly, a mechanistic analysis of power flow non-convergence and adjustment strategies is conducted, and metrics for evaluating the non-convergent power flow adjustment behavior dataset are proposed. Secondly, the fundamental principles and architectural features of the Conditional Generative Adversarial Network (CGAN) and Long Short-Term Memory (LSTM) network are introduced. Then, a data-driven augmentation method for the non-convergent power flow adjustment behavior dataset is presented. By incorporating an extreme value theory mechanism, the training capability of the CGAN on the training data is enhanced. Furthermore, LSTM is embedded into the GAN framework to strengthen the learning and capture capability of multi-dimensional features during the non-convergent power flow adjustment process. Finally, case studies are used to validate the effectiveness of the proposed method. The generated dataset of non-convergent power flow adjustment behavior can effectively characterize the complete closed-loop process of a power grid transitioning from an ill-conditioned state back to a solvable state, providing a crucial training and verification foundation for power flow optimization practices.